Effects of SGLT2 inhibitors on hepatic fibrosis and steatosis: A systematic review and meta-analysis - Zhou, Peipei; Tan, Ying; Hao, Zhenning; Xu, Weilong; Zhou, Xiqiao; Yu, Jiangyi (Frontiers in Endocrinology, 2023)
Objective: Clinical trials have shown sodium-glucose cotransporter 2 inhibitors (SGLT2i) are closely associated with hepatic fibrosis and steatosis by using Fibroscan. This paper aimed at evaluating the effects of SGLT2i on hepatic fibrosis and steatosis, presented as liver stiffness measurement (LSM) and controlled attenuation parameter (CAP). Methods: PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure Database, China Science and Technology Journal Database and Wanfang Database, were searched for randomized clinical trials from database establishment to 30 November 2022 with no language restrictions. Risk of bias was evaluated by Collaboration Handbook. Software Stata 17 and Review Manager (version 5.3) were used for meta-analysis. Results: A total of eight articles including 686 patients were included. Compared with control group, our results showed that SGLT2i could lower levels of LSM [MD =-0.82, 95%CI (-1.38, -0.25), p=0.005] and CAP [MD =-12.80, 95%CI (-20.57, -5.03), p=0.001]. Further subgroup analyses indicated that SGLT2i presented more advantageous on longer treatment duration and more serious steatosis in decreasing LSM. For CAP, SGLT2i exhibited clear advantage in subgroup analyses of longer treatment duration, younger people, dapagliflozin, worse fibrosis and steatosis. Conclusion: SGLT2i could reduce LSM and CAP in contrast to other antihyperglycemic drugs. However, the included studies are not definitive and well-designed, more multi-centered, blinded randomized clinical trials are warranted to definitively establish the reliable evidence.